Penerapan Media Digital dalam Mengatasi Kurangnya Konsentrasi Minat Belajar Siswa Terhadap Pembelajaran IPS SD - Amelia Reski Rulfani; Adrias Adrias; Salmaini Safitri Syam (Universitas Maritim AMNI Semarang, 2025)
This study aims to study the results of the application of digital media in overcoming the lack of concentration of students' interest in learning Social Sciences (IPS) in Elementary Schools. In IPS lessons there are various sciences about social and society, of course it is important to learn. The method used is a case study with a qualitative approach involving homeroom teachers and students. The results of the data obtained were taken by interviewing teachers and students involved in SDN 02 Situjuah Ladang Laweh, then data through direct observation results in the field along with documentation of teacher teaching to students. The results of this study have a fairly good impact on students, because teachers can combine learning with digital media that are currently developing. For example, such as showing interactive animated videos that can help students to concentrate on learning compared to previous teaching methods, interactive quizzes as evaluation results that can help improve students' understanding in understanding the material. Thus, the use of digital media has a good influence on the concentration of students' interest in learning IPS which can make students actively contribute to learning.